To reflect the triangle \( \triangle ABC \) across the y-axis, we need to change the sign of the x-coordinates of each vertex, while keeping the y-coordinates the same.
Given the vertices:
- \( A = (5, -1) \)
- \( B = (5, -9) \)
- \( C = (2, -7) \)
The reflected vertices will be:
- \( A' = (-5, -1) \)
- \( B' = (-5, -9) \)
- \( C' = (-2, -7) \)
So the new coordinates after reflecting across the y-axis are:
- \( A' = (-5, -1) \)
- \( B' = (-5, -9) \)
- \( C' = (-2, -7) \)
Thus, the new triangle \( \triangle A'B'C' \) has the coordinates:
- \( A'(-5, -1) \)
- \( B'(-5, -9) \)
- \( C'(-2, -7) \)